PENYIMPANGAN MAKSIM RELEVANSI DALAM FILM “PENGUASA DUNIA” KARYA LULA ALBAH - Ramadhina, Aulya Sowmya; Fridayanti, Lucky Angel (Jurnal Online Baradha, 2024)
Abstract The maxim of relevance in the film "Penguasa Dunia” by Lula Albah is a form of language use in aspects of the principle of cooperation used in the characters conversations. This research has a purpose to describe form of the deviation from the maxim of relevance in the film "Penguasa Dunia" by Lula Albah. To achieve this goal, this research is a research that uses pragmatic studies. The theory used is the maxim of relevance cooperation principle according to Grice. The method used is descriptive qualitative with research and note-taking techniques. The source of data and data for this research is the film "Penguasa Dunia" by Lula Albah. Researchers are the main instrument in this research. Handphone, laptop, and stationery are supporting instruments. Data is collected through transcription, then classified, coding, analyzing, then concluded. The results of this research show that the film "Penguasa Dunia" by Lula Albah contains form of the deviations from the maxim of relevance with the purpose of assertive, directive, commissive, and expressive speech acts. Keywords: maxim of relevance, the deviation of maxim, speech purpose